Strategies for optimizing petroleum exploration : evaluate initial potential and forecast reserves - Knoring, L. D. (Lev Davydovich) (Gulf Pub., 1999)
Here is a valuable guide to appraise and develop petroleum resources. Geology largely determines exploration policy. This book analyzes the strategic connection between the two and shows how to improve decision making on appraising and developing petroleum resources. It examines and describes the internal patterns in finding oil and gas deposits and outlines a process to evaluate the resources. The book also provides a means for long-term reserve accrual forecasting and evaluation. It uses mathematical modeling as a method to evaluate the initial potential of an oil and gas region as well as a.